Atomic uranium modified graphdiyne as catalytic material for hydrogen evolution reaction: An interfacial descriptor led mechanistic study. (21st September 2020) - Bacha, Raza ullah shah; Cai, Hong-Xue; Wang, Jian-Qiang; Pan, Qing-Jiang
Abstract: Catalysis operated on supported single metal atom is considered as one of the vital efforts for chemical and energy conversion. Despite the enormous amount of research on single transition metal (TM) enhanced graphdiyne (GDY ) material, its modification with slightly depleted uranium remains unexplored. Herein, we conducted relativistic density functional theory (DFT) calculations for the accumulation of atomic uranium inside size-suitable GDY pore. The stability of graphdiyne-uranium (GDY-U ) is corroborated in terms of short U–C bond distances (2.34–2.44 Å), with local depletion of charge and greater U(5f)-C(p) molecular orbital overlap. The magnificent structural and electronic properties of GDY-U system qualify it for the investigation of hydrogen evolution reaction (HER). The HER performance of all exposed sites, including central metal atom and four dissimilarly coordinated acetylenic carbons has been examined and compared with that of pure GDY . As the overall HER interfacial descriptor, free energy change of the intermediate state (ΔGH∗ ) at the central metal surface of GDY -U was found to be most favorable (0.153 eV) amongst all sites and far superior to those of pure GDY . In addition to the uranium surface, the coordinated carbons also show improved HER activity, indicating the enhancement of the system upon metal insertion. The calculated ΔGH∗ of the GDY -U system here is comparable to some of the recently reported GDY -TM materials, suggesting that atomic uranium could be an exceptional alternative for applied common catalysts. Graphical abstract: The atomic-uranium was encapsulated into graphdiyne, leading to the activation of central metal and connected carbons (C1, C2, C3, C4). The free energy for the Volmer step at uranium is 0.153 eV, while the molecular H2 formation is favored by Volmer-Tafel route. Image 1 Highlights: Graphdiyne-uranium as single-atom-catalysis material shows good HER performance. Strong-Metal-Support-Interaction with great U(5f)-C(2p) overlap and localization. Activation of all exposed sites including metal surface and connected carbons. GH∗  = 0.153 eV at metal center and carbons shows superiority for overall HER. Volmer-Tafel is slightly favored over Volmer-Heyrovsky at the metal surface.